New Possibilities for Planning the Recovery of Abandoned Agricultural Land in Mediterranean Mountain Communities: The Case of Troodos in Cyprus - Dimitris Goussios; Dimitra Gaki; Prodromos Mardakis; Ioannis Faraslis (Land)
This paper addresses the issue of abandoned agricultural land (AAL) as a phenomenon whose containment is crucial due to its extent, the agro-ecological transition, and the development challenges faced by mountain communities. The research is organised on two levels: (a) the mountain region of Troodos, Cyprus, where the stance of local communities regarding the impacts of abandonment is investigated, and (b) representative communities where the findings from the diagnosis, with the contribution of spatial analysis, are used as a guide in planning the process of recovering AAL. At this scale, an interactive methodology is proposed that incorporates the spatial and production dimensions through a “zone for recovery”. The paper results in a recovery process based on the correspondence between the differentiated agricultural land uses in mountains (intensive/extensive models, self-consumption, management, etc.) and the various user groups (existing and potential farmers, diaspora, etc.). This process indicates that, as long as there is a combined institutional intervention by communities, spatial planning, and local governance, integrating recovery into the local multifunctional production system leads to its differentiation and increased resilience.